Mitigation of Greenhouse Gas Emissions in Vehicle Routing Problems with Backhauling - Parada-Daza, V (2013)
In this paper, the decrease in the emission of greenhouse gases is evaluated using the vehicle routing problem with backhauls and time windows by considering the energy required for each route and estimating the load and distance between customers. Using a scatter search, problems from the literature with up to 100 randomly distributed customers were analyzed. Our results indicate that the distance traveled and the transportation costs increase as the required energy decreases, but the amount of fuel consumed also decreases; therefore, the emission of greenhouse gases also decreases. In some cases, the number of vehicles remains the same or increases because a better solution is achieved with shorter, better distributed routes. In addition, using a cooperative game approach, we found that different transportation companies operating jointly results in decreased emissions as well as operating costs. © 2013 Elsevier B.V. All rights reserved.